2010
DOI: 10.1161/circresaha.110.221242
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of Nox4 by TGFβ1 Oxidizes SERCA and Inhibits NO in Arterial Smooth Muscle of the Prediabetic Zucker Rat

Abstract: Rationale: Vascular smooth muscle cell (SMC) migration is an important pathological process in several vascular occlusive diseases, including atherosclerosis and restenosis, both of which are accelerated by diabetes mellitus.Objective: To determine the mechanisms of abnormal vascular SMC migration in type 2 diabetes, the obese Zucker rat (ZO), a model of obesity and insulin resistance, was studied. Key Words: nitric oxide Ⅲ cell migration Ⅲ NADPH oxidase Ⅲ obese Zucker rat Ⅲ TGF-␤1 Ⅲ Smad2 D iabetic patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 44 publications
6
109
0
Order By: Relevance
“…Nevertheless, association of Nox4 to the ER seems highly likely, but the exact function of the enzyme in this organelle remains to be clarified. The potential targets of Nox4-derived hydrogen peroxide in the ER include protein-tyrosine phosphatase 1B [117,118], sarco/endoplasmic reticulum Ca 2+ -ATPase [119] and ryanodine receptor [118].…”
Section: Formation and Elimination Of Hydrogen Peroxide In The Ermentioning
confidence: 99%
“…Nevertheless, association of Nox4 to the ER seems highly likely, but the exact function of the enzyme in this organelle remains to be clarified. The potential targets of Nox4-derived hydrogen peroxide in the ER include protein-tyrosine phosphatase 1B [117,118], sarco/endoplasmic reticulum Ca 2+ -ATPase [119] and ryanodine receptor [118].…”
Section: Formation and Elimination Of Hydrogen Peroxide In The Ermentioning
confidence: 99%
“…1 We found that the adenoviral vector intended to express human wild type SERCA2b in the experiments shown in Figure 1b in this paper actually encoded the SERCA2b C674S mutant and in addition was contaminated with E1A adenovirus. The incorrect adenoviral vector was identified by PCR of the full-length SERCA present in the viral DNA within infected cells.…”
mentioning
confidence: 71%
“…The methods are provided in full in Tong et al 1 and Haeussler et al 2 Titers of the new wild type SERCA 2b and the SERCA 2b C674S mutant were adjusted so that both increased mRNA levels 2-to 3-fold over baseline with an equal increase in SERCA protein expression confirmed by western blot. In the figure below, cultured Obese Zucker rat aorta smooth muscle cells infected with an "empty" adenoviral vector, which lacks a gene insert, migrated similarly in response to serum as the cells infected with the LacZ vector used as control in the original Figure 1b of Tong et al Cells infected with authentic wild type SERCA2b showed similar migration, but demonstrated a restoration of the ability of the nitric oxide donor, DETA NONOate, to inhibit their migration into a scratch wound (see Figure 1 below).…”
mentioning
confidence: 99%
“…9,10 For example, in obese Zucker rats, a model of obesity and insulin resistance, common carotid injury was attenuated by Nox4 knockdown with Nox4 short hairpin RNA, implicating Nox4 in neointimal formation and vascular injury. 10 Pharmacological inhibitors of Nox4 (VAS2870 and GKT136901) also prevented agonist-induced oxidative stress and inflammatory responses in cultured cells. 11,12 However, these observations are merely suggestive of Nox4 in vascular pathology and by no means establish cause and effect.…”
Section: Article See P 1217mentioning
confidence: 99%
“…First, in the study of Schroder et al, 14 vascular functional studies were performed in large conduit vessels (aorta) and in lung endothelial cells from Nox4-deficient mice, whereas many previous studies explored small arteries and cultured vascular smooth muscle cells. 3,5,9,10,11,17,18 Second, in Nox4 knockout mice, the gene deletion is global, and, accordingly, it is not entirely correct to implicate a vascular-specific pathology in a model in which there is a ubiquitous knockout. Third, the fact that it is only in challenged conditions that Nox4 knockout mice exhibit a vascular phenotype indicates a nonessential role of Nox4 in physiological conditions.…”
Section: Article See P 1217mentioning
confidence: 99%